NOTE ON THE ANALYSIS OF SIZE FREQUENCIES OF SETIPINNA TATY (VALENCIENNES) OF THE LOWER SUNDERBANS REGION (HOOGHLY-MATLAH ESTUARY) - Datta, D K; Datta, P (Indian Journal of Fisheries, 2011)
Large scale fishing takes place around Frazerganj in the Hooghly-Matlahestuary with the ht;lp of bagnets (Pillay and Ghosh, 1962), locally known as'binjal' or 'behundi jal', during the winter season. A substantial portion of thecatch obtained consists of Setipinna spp. mostly S. taiy. During 1969-'70 and1970-'71 the catches of Setipinna species were 249 tonnes and 420 tonnes forming14.05% and 14.09% of the total landings during the season and 51.33%and 52.25% respectively of the total annual catch of the species from the entireHooghly-Matlah estuary. The length frequencies of 5. taty, from these catcheswould give a good indication of the age-structure of the total catch from theestuary, besides gi\ing an idea of the age-structure of the seasonal populationof the species in the particular area.